Analisis Risiko Keterlambatan pada Proyek Konstruksi Villa Tretes dengan Metode Bayesian Belief Network - Satrio Tri Atmojo; Masca Indra Triana (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The Villa Tretes construction project in Prigen District, Pasuruan Regency, faces various potential risks of delay influenced by both technical and non-technical factors during the project implementation process. This study aims to identify the risk factors affecting project delays and to determine the probability levels of delay risks using the Bayesian Belief Network (BBN) method. The research was conducted using a quantitative approach through the distribution of questionnaires and interviews with 22 respondents directly involved in the project. The research data was analyzed using the Bayesian Belief Network method with the assistance of HUGIN Lite software to determine the probabilistic relationships among project delay risk factors. The results indicate that the factors with the greatest influence on project delays are finance and administration (84.49%), project documentation (84.10%), and labor (83.565%). The analysis results indicate that these factors have a significant correlation with the potential for project delays, thus requiring attention in the control of construction work implementation.